Using the Matlab App to Detect Objects by Color with HSV Color Segmentation - Rindi Antika; Muhammad Iqbal (Jurnal Mantik, 2022)
Object detection using computer vision algorithms is a crucial procedure for accurately detecting items in a three-dimensional image. When using the color segmentation method with HSV color, an image segment object in the shape of a blob is created, which the computer can detect. The color sample will provide a value that will be the reference for the filter range in the segmentation process based on the test findings. During the process, the number of objects identified according to the given color will be determined.